Estudo microfaciológico e quimioestratigráfico de calcários do Grupo Macaé a partir de uma seção distal da Bacia de Campos - Caetano Filho, Sergio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Late Aptian-Early Albian marine limestones from the basins of eastern Brazilian Continental Margin record the early stages of the South Atlantic Ocean (SA). Fossil assemblages and geochemical signatures of these rocks indicate marine incursions from Tethys paleocean in this restricted sea, with organic-rich sediments and planktic foraminiferal bioevents registered. The Late Aptian-Early Albian transition is marked by paleoclimatic and paleoceanographic changes which resulted in global carbon cycle perturbations. The investigation of this interval at the SA and its stratigraphic correlation with coeval sections promote a better understanding and temporal definition of the geological processes that occurred in this setting, which are fundamental to petroleum exploration. This work presents the chemostratigraphy and microfacies analysis of a distal section of the Macaé Group (Late Aptian-Cenomanian), in Campos Basin, focusing on the paleoenvironmental characterization and global correlations to the base of this unit. The study of microfacies was carried out by petrography, cathodoluminescence and SEM/EDS analysis. The chemostratigraphy encompassed C, O and Sr isotopes, major, minor and trace elements, TOC and pyrolysis analysis. The results allowed the section division into six informal units, I to IV (bottom to the top), and its association with Quissamã and Outeiro formations, which record a gradual platform drowning and more humid climate conditions. Six microfacies were identified in units I and III, which were grouped in five microfaciological associations in a carbonate ramp model. In unit I, the microfacies are composed by benthic-dominated wackestones and packstones (CCB and C*CB) deposited on the inner-ramp/inter-bank and its flanks (AM-1 and AM-2, respectively), in a proximal and oxygenated environment. The microfacies from unit III (CPP, C*PP and C*RP) are composed by planktic-dominated mudstones and wackestones, deposited on the...

Calcários marinhos neoaptianos-eoalbianos das bacias da Margem Leste Brasileira registram as fases iniciais de instalação do primitivo Oceano Atlântico Sul (AS). Associações fossilíferas e assinaturas geoquímicas presentes nestas rochas apontam para influência de águas do paleoceano Tétis sobre este mar restrito, com preservação de matéria orgânica e bioeventos de foraminíferos planctônicos associados. O intervalo Aptiano superior-Albiano inferior é marcado por mudanças climáticas e paleoceanográficas responsáveis por perturbações no ciclo global do carbono e sua investigação no AS e correlação com seções contemporâneas possibilitam melhor compreensão e definição temporal dos processos atuantes neste contexto, fundamentais para exploração petrolífera. Este trabalho apresenta o estudo quimioestratigráfico e microfaciológico de uma seção distal do Grupo Macaé (Neoaptiano-Cenomaniano), Bacia de Campos, visando à caracterização paleoambiental e correlações globais para a base desta unidade. O estudo microfaciológico envolveu petrografia e catodoluminescência óptica, análises em MEV/EDS, enquanto a quimioestratigrafia utilizou isótopos de C, O e Sr, elementos maiores, menores e traços, COT e pirólise. Os resultados permitiram a divisão da seção em seis unidades informais, I-VI (base para o topo), associadas às formações Quissamã e Outeiro, que registram o progressivo afogamento da plataforma e clima mais úmido. O estudo microfaciológico das unidades I e III identificou seis microfácies, agrupadas em cinco associações microfaciológicas dispostas em modelo de rampa carbonática. As microfácies correspondentes à Unidade I (CCB e C*CB), compostas por wackestones e packstones bioclásticos ricos em organismos bentônicos, foram dispostas em rampa protegida/interbanco e flancos de banco (AM-1 e AM-2, respectivamente), como ambiente mais proximal e oxigenado. As microfácies da Unidade III...
Keywords: Geology, Stratigraphic; Geologia estratigráfica; Geoquimica; Facies (Geologia); Campos, Bacia de (RJ); Rochas carbonaticas; Petrologia